PRintability effect on ASAM Rumex extracted papers (handsheets) for vegetable-oil inks - (:unkn) unknown (Scibulcom Ltd., 2017)
ASAM (alkaline sulphite antraquinone methanol) method is one of environmentallyfriendly organosolv pulping generation methods. It was developed with Rumex extract and the obtained laboratory scaled handsheets were used with environmentallyfriendly vegetable oil inks to examine the printing features. To this end, handsheets were produced from the pulps from P. deltoides, Robinia pseudoacacia and Pinus pinaster woods obtained by using Rumex crispus L. extracted in the ASAM cooking method. These papers were examined in terms of their printability features in layer offset printing system by using conventional oil-based inks for control with vegetable oil (soybean, soy + flax seed) based inks. According to the results of the tests made, P. deltoides was the lowest with air permeability and Pinus pinaster was the highest in terms of the same. Robinia pseudoacacia has high entering with contact angle, and roughness of paper is the highest in P. deltoides and Robinia pseudoacacia has the lowest. In terms of the printability properties of handsheets, it was determined that P. deltoides has both high print optical density and print chrome much higher than the others. It was seen that the printing results made with the vegetable oils had very close values to the printing results of mineral oiled inks. These features will prevent formation of harmful components that may form with migration in packages of vegetable oils and they will contribute to protection of human health and environment.
Keywords: ASAM with Rumex; Mineral oil inks; P. deltoids; Printability; Robinia pseudoacacia and Pinus pinaster